1997
DOI: 10.1002/eji.1830270620
|View full text |Cite
|
Sign up to set email alerts
|

HTLV‐I‐infected T cells activate autologous CD4+ T cells susceptible to HTLV‐I infection in a co‐stimulatory molecule‐dependent fashion

Abstract: A vigorous production of human T lymphotropic virus type I (HTLV-I)-infected CD4+ T cells is closely associated with the development of adult T cell leukemia (ATL) and neurological disease. However, the immunological mechanisms leading to generation of the HTLV-I-infected cells are not fully clarified. The modulation of CD80 and CD86 expression on the HTLV-I-infected cells and its physiological role in the interaction of infected CD4+ T cells with uninfected CD4+ T cells was examined. The HTLV-I-infected CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Additional candidate B lymphocyte surface molecules include CD80 and CD86, as expression of these molecules on antigen-presenting cells are critical costimulatory molecules for full CD4 T lymphocyte activation and effector function (28,29). Of interest is the observation that HTLV-I/II infection leads to constitutive expression of both CD80 and CD86 on human T lymphocytes and that the CD80/86ϩ HTLV-infected T lymphocytes stimulate proliferation of autologous resting T lymphocytes (30,31). This suggests that expression of these molecules in the context of HTLV infection promotes CD4 T lymphocyte activation independent of antigen-MHC-II-mediated signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Additional candidate B lymphocyte surface molecules include CD80 and CD86, as expression of these molecules on antigen-presenting cells are critical costimulatory molecules for full CD4 T lymphocyte activation and effector function (28,29). Of interest is the observation that HTLV-I/II infection leads to constitutive expression of both CD80 and CD86 on human T lymphocytes and that the CD80/86ϩ HTLV-infected T lymphocytes stimulate proliferation of autologous resting T lymphocytes (30,31). This suggests that expression of these molecules in the context of HTLV infection promotes CD4 T lymphocyte activation independent of antigen-MHC-II-mediated signaling.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that HTLV-1-infected T cells express cell surface molecules related to T-cell activation (4,29,41,48). Thus, we examined the expression of MHC-I, MHC-II, CD25, CD80, and CD86 on FPM1B-siTax27 cells to determine whether the evasion of Tax-specific CTLs was associated with the expression levels of these molecules.…”
Section: Resultsmentioning
confidence: 95%
“…This may be due to the direct effect of the repression of Tax expression because HTLV-1-infected T cells are known to express these molecules (18,48). Since MHC-II expressed on HTLV-1-infected T cells plays a role in the activation of helper T cells (48), it is possible that this downregulation could also result in the reduction of HTLV-1-specific immune responses. On the other hand, FPM1B-siTax27 and FPM1B.siTax32 cells did not show the downregulation of CD80, CD86, and MHC-I, whose expression is also shown to be induced by Tax (4,41).…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1-infected CD4þ T-cell lines established from ATLL patients and normal donors by infecting their CD4þ Tcells with the virus express CD80, CD86, and HLA-DR, and induce proliferation of autologous and allogenic CD4þ T-cells (Takamoto et al, 1997). The induction of proliferation of noninfected CD4þ cells has been suggested as a mechanism to generate additional targets for spread of HTLV-1 infection to uninfected lymphocytes (Goon et al, 2004).…”
Section: Immune Responses To Infectionmentioning
confidence: 99%
“…Both HTLV-1 and HTLV-2 infections are associated with spontaneous proliferative responses in vitro, which can be observed early in the course of infection (Goon et al, 2004;Takamoto et al, 1997). HTLV-1-infected CD4þ T-cell lines established from ATLL patients and normal donors by infecting their CD4þ Tcells with the virus express CD80, CD86, and HLA-DR, and induce proliferation of autologous and allogenic CD4þ T-cells (Takamoto et al, 1997).…”
Section: Immune Responses To Infectionmentioning
confidence: 99%